2008
DOI: 10.1002/jcp.21428
|View full text |Cite
|
Sign up to set email alerts
|

P53 mutations in colorectal cancer from northern Iran: Relationships with site of tumor origin, microsatellite instability and K‐ras mutations

Abstract: CRC-associated P53 mutations have not been studied extensively in non-Western countries at relatively low CRC risk. We examined, for the first time, 196 paraffin-embedded CRC cases from Northern Iran for mutations in P53 exons 5-8 using PCR-direct sequencing. P53 status and mutation site/type were correlated with nuclear protein accumulation, clinicopathologic variables and data on K-ras mutations and high-level microsatellite instability (MSI-H). We detected 96 P53 mutations in 87 (44.4%) cases and protein ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 43 publications
(82 reference statements)
3
24
0
Order By: Relevance
“…These include seven variants previously classified as polymorphisms in IARC TP53 database and two novel variants. The silent c.903A[G mutation was previously found in three somatic tumors other than breast [32][33][34] and now it was detected for the first time in the germ line. It was identified in a patient of Punjabi origin, who was diagnosed with breast cancer at 27 years of age, but not in 112 healthy controls.…”
Section: Resultsmentioning
confidence: 95%
“…These include seven variants previously classified as polymorphisms in IARC TP53 database and two novel variants. The silent c.903A[G mutation was previously found in three somatic tumors other than breast [32][33][34] and now it was detected for the first time in the germ line. It was identified in a patient of Punjabi origin, who was diagnosed with breast cancer at 27 years of age, but not in 112 healthy controls.…”
Section: Resultsmentioning
confidence: 95%
“…TP53 alterations are identified as late events in CRC development, with a loss of TP53-mediated apoptotic pathways as an important factor in the progression from an adenoma to a malignant tumor (Smith et al, 2002). The frequency and spectrum of TP53 alterations were associated with the different grades, stages and locations of the tumor (Mahdavinia et al, 2008). A study by Mahdavinia et al (2008) found that the frequency of TP53 mutations significantly increased with tumor stages (36/94, 38.3%; 33/64, 51.5%, and 15/23, 65.2% in Stage B, C, and D, respectively) and this is also reflected in our finding.…”
Section: Discussionmentioning
confidence: 99%
“…In case of its mutation, this regulation could be lost, resulting in cell proliferation without control and development of cancer. TP53 mutation has been reported to have an association with risks of several cancers such as lung cancer [12], breast cancer [13], and colorectal cancer [14]. The loss of TP53 gene could damage its DNA-binding properties and transcription factor function, thus leading to aberrant cell proliferation.…”
Section: Introductionmentioning
confidence: 99%